Peran Inovasi dan Teknologi dalam Manajemen Rantai Pasok Berkelanjutan pada Industri Agrifood: Tinjauan Literatur - Alif Hasna Astrima; Nia Jessica Lona; Wayan Ardi Adnyana; Yanti Nuraeni Muflikh; Suprehatin Suprehatin (Jurnal Agribisnis Indonesia, 2025)
The agrifood industry faces complex challenges in creating a sustainable supply chain. Sustainable Supply Chain Management (SSCM) serves as a strategic approach that integrates economic, environmental, and social aspects in supply chain governance. This study analyze the contribution of innovation and digital technologies to the sustainability dimensions of SSCM within the agrifood industry using a Systematic Literature Review (SLR) of 67 recent scientific publications (2020–2025) from the Scopus and ScienceDirect databases. The findings show that sustainability-oriented innovations such as precision farming, green technologies, and collaborative approaches play a crucial role in transforming conventional supply chains into more efficient, inclusive, and adaptive systems. Technologies such as blockchain, Internet of Things (IoT), and Artificial Intelligence (AI) have proven effective in enhancing operational efficiency, traceability, resource management, and food safety. Innovation strengthens collaboration among supply chain actors and accelerates the adoption of environmentally friendly practices. However, challenges remain regarding infrastructure readiness, resistance to technology adoption, and collaboration. Therefore, the strategic utilization of innovation and technology holds potential to accelerate digital transformation and enhance the resilience and sustainability of the agrifood system. This study highlights that the utilization of technology and innovation in supply chain management drives sustainability transformation in the agrifood industry. However, the success requires improved human resource capacity, adequate infrastructure, and strong synergy among actors. Supportive policies, increased investment in infrastructure—particularly in rural areas—and strengthened collaboration are essential to ensure an inclusive and sustainable digital transformation within SSCM.